THE STUDY ON INFLUENCE OF FAMILY OWNERSHIP AND ENTREPRENEURIAL ORIENTATION ON FORMAL PLANNING IN SME - Kariyawasam, A.H.N. (My University, 2019)
This study aims to analyze the differences in formal planning in Small and Medium Enterprises (SME) and the influence of family ownership and Entrepreneurial Orientation on these differences. Many studies have explained the importance of the management accounting practices such as short term and long term budgeting, but the differences in those techniques will determine the success and the failure of a SME. SME are an important part of the Sri Lankan economy as they contribute to more than 50% of the GDP. Therefore it is important to see how family ownership and Entrepreneurial Orientation will affect budgets of an SME and its financial performance. This research was conducted in Western province in Sri Lanka, using the survey method for 55 SMEs. Regression and correlation analysis were used to analyze the data. Results found through this study suggests that family owned SMEs use budgeting techniques to a lesser extent and higher the EO level of a SME higher the usage of short term and long term budgets would be. There were not many studies to find out the differences in budgeting used in SME. This study is one of the few studies to be conducted in Sri Lanka to find out the differences in budgeting used in SME.
Keywords: Budgeting, SME, EO, Family ownership, Planning, Accounting